2015
DOI: 10.1177/2053369115574448
|View full text |Cite
|
Sign up to set email alerts
|

Sex, women and the menopause: Are specialist trainee doctors up for it? A survey of views and attitudes of specialist trainee doctors in Community Sexual & Reproductive Health and Obstetrics & Gynaecology around sexuality and sexual healthcare in the (peri)menopause

Abstract: Sexual health, function and pleasure can contribute significantly towards the wellbeing of (peri-)menopausal women. Healthcare professionals specialising in women's health should therefore be able to provide 'sex-positive' menopause care, which proactively addresses any sexual issues and assesses the need for contraception and prevention of sexually transmitted infections. A survey was used to investigate the views and attitudes of specialist trainee doctors in Community Sexual & Reproductive Health (cSRH) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Evidence is growing which suggests that older adults do not always seek help for sexual difficulties (see Hinchliff & Gott, 2011), and that health professionals do not routinely ask older patients about sex due to reasons including a lack of confidence, discomfort and feeling deskilled (Gleser, 2015;Mellor et al, 2013;Wei & Mayouf, 2009). Given that sex can be a quality of life issue for older adults, and that they may experience sexual difficulties but not receive appropriate care, it is important to explore the area further and increase our understanding.…”
Section: Sexual Difficultiesmentioning
confidence: 99%
“…Evidence is growing which suggests that older adults do not always seek help for sexual difficulties (see Hinchliff & Gott, 2011), and that health professionals do not routinely ask older patients about sex due to reasons including a lack of confidence, discomfort and feeling deskilled (Gleser, 2015;Mellor et al, 2013;Wei & Mayouf, 2009). Given that sex can be a quality of life issue for older adults, and that they may experience sexual difficulties but not receive appropriate care, it is important to explore the area further and increase our understanding.…”
Section: Sexual Difficultiesmentioning
confidence: 99%
“…However, knowledge was limited and of the studies that specified the approach to sexuality, most did not address the presence of proactivity. 4,[7][8]11 An article 10 showed that 96.7% of geriatrics consider it important to manage sexual problems, but 43% did not address sexual history, and the same article showed that U.S. gynecologists had less permissive attitudes than Turkish doctors and Australian nurses.…”
Section: Resultsmentioning
confidence: 99%
“…5 Studies show that the elderly continue to experience sexual interest and wish to maintain their sexuality. [5][6][7] The subject of sexuality in aging, however, is still surrounded by prejudice from the youngest, the elderly and many health professionals, being an area of gerontology little addressed. There are many cultural myths that can result from the portrayal of the media and many common beliefs such as asexual old age and the sexually undesirable and frail elderly, by physical changes and funny connotations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many recommendations available, an electronic survey of UK GPs found that the majority lacked confidence in effectively managing peri-and postmenopausal women [45]. Similarly, trainees in obstetrics and gynaecology have been shown to be insufficiently qualified for post-reproductive bone healthcare (Switzerland) [46], sexual healthcare (UK) [47] and core menopause topics (USA) [48]. These findings are not surprising given the rapid changes in opinion on the benefits and risks of MHT during the past decade, which has caused confusion among healthcare providers and women.…”
Section: Current Healthcare Provision For Menopausal Womenmentioning
confidence: 99%